Element Of Risk. - DONALD, ROBYN; Mills & Boon Classics (Sydney, New South Wales : HarperCollins Publishers, 2024)
‘I thought I was rid of you — why the hell did you have to come back?’ It was eleven years — two lifetimes ago — since Perdita Gladstone and Luke Dennison had met last. Now the legacy of their shared past required another encounter. Perdita was no longer a gawky girl, but an assured woman with an international career. But did she have the confidence to handle a man like Luke, who made it clear that her reappearance in his life was not a welcome one?.
General
Keywords: Contemporary romance; Fiction - Romance - Contemporary; Electronic books